Seismic response evaluation of an urban overpass. - Mayoral, Juan M. (Earthquake engineering & structural dynamics.)
The seismic response of one section of a 23 km strategic urban overpass to be built in the so-called transition and hill zones in Mexico City is presented. The subsoil conditions at these zones typically consist on soft to stiff clay and medium to dense sand deposits, randomly interbedded by loose sand lenses and underlain by rock formations that may outcrop in some areas. Several critical supports of this overpass are going to be instrumented with accelerometers, inclinometers and extensometers, tell tales and end pile cell pressures to assess their seismic performance during future earthquakes and to generate a database to calibrate soil structure interaction numerical models. This paper presents the seismic performance evaluation of the critical supports located in one section of the overpass. Sets of finite elements models of the soil-foundation-structure systems were developed. Initially, the model was calibrated analyzing the seismic response that an instrumented bridge support exhibited during the June 15th, 1999 Tehuacan (Mw=7) Earthquake. This bridge is located also within the surroundings of Mexico City, but in the lake zone, where highly compressible clays are found. The computed response was compared with the measured response in the free field, pile box foundation and bridge deck. Once the model prediction capabilities were established, the seismic response of the critical supports of the urban overpass was evaluated for the design earthquake in terms of transfer functions and displacement time histories.